Reasoning from Faith: Fundamental Theology in Merold Westphal's Philosophy of Religion - Sands, Justin (Indiana Series in the Philosophy of Religion Ser, 2018)
Cover -- REASONING FROM FAITH -- Title -- Copyright -- Dedication -- CONTENTS -- Acknowledgments -- Abbreviations -- Introduction -- 1 Of Hermeneutics and Style: How to Read Westphal -- 2 Recontextualization: A Westphalian Aufhebung? -- 3 Westphal and Hegel: Judging Religion through Politics -- 4 Hegelians in Heaven, but on Earth . . . : An "Unfounding," Kierkegaardian Faith -- 5 Religiousness: The Expression of Faith -- 6 Faith Seeking Understanding: Westphal's Postmodernism -- 7 Intermediary Conclusions: The Believing Soul's Self-Transcendence -- 8 Radical Eschatology: Westphal, Caputo, and Onto-theology -- 9 Comparative Eschatology: Westphal's Theology, Kearney's Philosophy, and Ricoeurian Detours -- Conclusion: Westphal as a Theologian and Why It Matters -- Bibliography -- Index.